From Sun to Roof to Grid : Distributed PV in Energy Sector Strategies - Energy Sector Management Assistance Program (World Bank, Washington, DC, 2021)
As the world’s fastest-growing local energy technology, distributed photovoltaics (DPV) has upended the traditional paradigm of one-way power flow from the grid to consumers. Solar electricity systems located close to grid consumers known here as DPV empower consumers to produce electricity for themselves and for the grid. Thanks mainly to falling PV costs, DPV has become a viable way to meet energy needs for a widening array of consumers. Worldwide, installed capacity of DPV exploded from just a few megawatts (MW) in 2000 to 250 gigawatts (GW) in 2019; and it is forecast to exceed 500 GW by 2025. Poorly managed, DPV scale-up can then erode utility finances and interfere with grid operation. Yet, as explained in this report, well-managed DPV can benefit not only DPV owners but also contribute to reliable grid operation and a financially sound electricity sector. DPV offers multiple types of benefits relevant for low- and middle-income countries, especially when it can reduce electricity costs and widespread dependence on diesel generators. This report is an overview of DPV in different country contexts, and it is aimed at energy ministries and other decision-makers. Chapter 1 introduces key concepts and the recent status of the DPV market. It also highlights key potential value propositions of DPV for different stakeholders, including consumers, utilities, governments, and society as a whole. Chapter 2 presents nine specific ways in which distributed photovoltaics (PV) is or could be used to solve problems faced in low and middle-income country contexts.